Sustainbale Innovation Competency among Supervisors in Textile Mills in Erode - Dr. N. Kumarasamy, P.Kamalanathan (International Journal of Advanced Science and Technology, 2019)
In a past decade of innovation, companies have come to understand that innovation is an important issue in sustainable business management, as it helps improve capabilities and competencies of their company. Because of the fiercely competitive environment in the textile industry, the need of innovation among the supervisors has become a critical factor in the process of productivity differentiation, leading to sustainable business success.In particularly textile industry need skilled supervisors for managing competitive market. In this research, Amarjothi Spinning Mills is selected, it is one of the major textile mill in Erode District. From the company, 48 supervisors have selected for examining their competency performance. Questionnaire is the main tool for data collection. The collected data were subdued into tables and charts with the help of SPSS 22.0. Statistical tools like Percentage Analysis, Mean Score Analysis andAnovaAnalysis. The results showed that 36-45 years aged supervisors have more productivity with innovation that leads to sustainable business development of the textile mills.Keywords : Sustainable Business development, Innovation Competency, Skills, Knowledge, Work Force.